Penundaan Tahapan Pelaksanaan Pemilihan Kepala Daerah (Pilkada) Sebagai Dampak Covid-19 Dilihat Dari Aspek Hukum Ketatanegaraan - Esti Ningrum (Faculty of Law, Universitas Wijayakusuma, 2020)
The delay phase of the election of Regional Head (elections) as the impact COVID-19 from the aspect of constitutional law has mendapatan legal basis ie Government Regulation in Lieu of Law (Perppu) No. 2 of 2020 concerning Third Amendment Act No. 1 of 2015 concerning Establishment of Government Regulation in Lieu of Law Number 1 of 2014 concerning Election of Governors, Regents and Mayors Into Act.2. Preparation of regulations in anticipating problems that arise in the postponement of the stages of the implementation of the election of Regional Heads as a result of COVID-19 has been regulated in Law Number 10 Year 2016 concerning Second Amendment to Law Number 1 Year 2015 concerning Establishment of Government Regulations Substituting Laws Number 1 of 2014.Keywords: The stages of implementing the Regional Head Election, Covid-19, Legal Aspects of ConstitutionalityÂ Abstrak. Penundaan tahapan pelaksanaan pemilihan Kepala Daerah (Pilkada) sebagai dampak COVID-19 dilihat dari aspek hukum ketatanegaraan telah mendapatan payung hukum yaitu Peraturan Pemerintah Pengganti Undang-Undang (Perppu) Nomor 2 Tahun 2020 tentang Perubahan Ketiga Atas Undang-Undang Nomor 1 Tahun 2015 tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2014 tentang Pemilihan Gubernur, Bupati dan Walikota Menjadi Undang-Undang. Persiapan regulasi dalamÂ mengantisipasi persoalan yang muncul dalam penundaan tahapan pelaksanaan pemilihan Kepala Daerah sebagai dampak COVID-19 telah diatur di dalam Undang-Undang Nomor 10 Tahun 2016 tentang Perubahan Kedua Atas Undang-Undang Nomor 1 Tahun 2015 tentang Penetapan Peraturan Pemerintah PenggantiUndang-Undang Nomor 1 Tahun 2014.Kata kunci : Tahapan pelaksanaan Pemilihan Kepala Daerah, Covid-19, Aspek Hukum Ketatanegararaan